"Watchful citizens" and digital vigilantism: a case study of the far right in Quebec. Issue 3 (1st October 2020) - Tanner, Samuel; Campana, Aurélie
ABSTRACT: Vigilantism is defined as collective coercive practices carried out by non-state actors and intended to enforce norms (social or judicial) or to act directly to enforce such actors' views of the law. Vigilantes are involved in both societal control and the fight against crime. In this article, we analyse how societal vigilantes use digital media (Facebook) to act on immigration, national identity, ethnic boundaries, and cultural values in the province of Quebec, Canada. We show how social media practices entail performative effects that should not be considered exclusively in terms of physical expression, such as gatherings of dispersed constituencies, as in, for example, the Arab Spring, but also in relation to the construction of boundaries and increased polarisation between social groups. These latter effects have real consequences, such as separating one element of the population (Muslims) from the moral obligation social groups have towards each other in society.